POST-HARVEST QUALITY PROFILE OF DRIED SEAWEED (KAPPAPHYCUS ALVAREZII) IN PASI KOLAGA DISTRICT, MUNA REGENCY, SOUTHEAST SULAWESI, INDONESIA - Iin Nurdiyanty Nurdin; Akhmad; Mohammad Natsir; Ary Tamtama; Dustan (Proceeding of International Seminar on Agricultural Conservation and Cultural Heritage, 2025)
Kappaphycus alvarezii is a leading commodity of aquaculture in Southeast Sulawesi, especially in Pasi Kolaga District, Muna Regency, which is the largest seaweed producing area in the province. Although it has high economic potential, its post-harvest quality is still not well documented. This study aims to examine the post-harvest quality of dried seaweed. Kappaphycus alvarezii through sensory, chemical, and physical evaluation. A quantitative approach was used with purposive sampling, involving three samples from different farmers with large stocks. Quality testing followed the Indonesian National Standard (SNI) 2690:2015 and 8169:2015 and was analyzed descriptively. Sensory analysis showed an average appearance score of 8.0 (slightly less clean, bright, species-specific) and a texture score of 7.5 (unevenly dry, tough, not easily broken), both meeting the minimum SNI standard of 7. Chemical analysis found an average moisture content of 35.50% and a CAW value of 46.82%, both of which did not meet the SNI standard (maximum moisture content of 30% and minimum CAW of 50%). Physical testing showed an average coarse impurity of 7.05%, exceeding the 3% limit. Other values ​​were: foreign matter 0.22%, sand 0.85%, salt 10.80%, and total impurity 10.67%. These results indicate that the post-harvest quality of seaweed has not fully met national standards, especially in chemical and physical aspects.